FhlA-mediated regulation of proton transport and energy transduction in Escherichia coli at acidic pH - Heghine Gevorgyan; Anait Vassilian; Anna Poladyan; Karen Trchounian (PLoS ONE, 2026)
In Escherichia coli, the FhlA acts as a transcriptional activator for fdhF , hyc and hyp operons, whose gene products constitute the formate hydrogen lyase (FHL) complexes. These complexes contribute to bioenergetic regulation by consuming intracellular protons during the conversion of formate to hydrogen gas (H 2 ). The current study elucidates the role of the FHL complex (using fhlA mutant) in the proton transport and energy transduction during the fermentation of glucose, glycerol and formate at pH 5.5. It was shown that F O F 1 -ATPase activity and proton flux rate were decreased in fhlA at 20 h and 72 h grown cells, compared to WT indicating the functional interplay between FHL and F O F 1 and highlighting its importance in proton transfer at acidic conditions. Increased number of membrane –SH groups and decreased proton conductance (C M H + ) value in both WT and fhlA mutant were detected at 72 h, compared to 20 h, suggesting efficient energy transduction at acidic pH when H 2 was not generated. The value of membrane potential (ΔΨ) remained unchanged in FhlA-lacking cells and was independent of growth time. Thus, bacteria regulate proton motive force (Δp) managing bioenergetic association between proton ATPase activity, FHL function and transmembrane proton gradient (ΔpH) regulation. Overall, these findings demonstrate that the FHL complex plays an essential role in coordinating proton flux, regulation of proton motive force and energy transduction in E. coli under acidic fermentative conditions through functional interplay with the F O F 1 -ATPase.